2021
DOI: 10.1002/ijgo.13793
|View full text |Cite
|
Sign up to set email alerts
|

Differential impact of COVID‐19 in pregnant women from high‐income countries and low‐ to middle‐income countries: A systematic review and meta‐analysis

Abstract: Background SARS‐CoV‐2 has infected a large number of pregnant women. Objective To compare clinical, perinatal outcomes of women with COVID‐19 from high‐income countries (HICs) and low‐ to middle‐income countries (LMICs). Search strategy Online databases were searched. Selection criteria Original studies on pregnant women with COVID‐19 were included. Data collection and analysis Information on clinical presentation, co‐morbidities, pregnancy outcomes, neonatal outcomes, and SARS‐CoV‐2 infection in neonates was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 41 publications
(88 reference statements)
5
54
0
2
Order By: Relevance
“…There is limited information on PTB rates in women with COVID‐19 in low‐ and middle‐income countries. A recent meta‐analysis reported the disproportionate impact of COVID‐19 on pregnant women residing in low‐ and middle‐income countries 7 . Earlier, we reported higher rates of intensive care unit admission and maternal mortality among pregnant women during the second wave of the COVID‐19 pandemic in India 8 .…”
Section: Introductionmentioning
confidence: 51%
“…There is limited information on PTB rates in women with COVID‐19 in low‐ and middle‐income countries. A recent meta‐analysis reported the disproportionate impact of COVID‐19 on pregnant women residing in low‐ and middle‐income countries 7 . Earlier, we reported higher rates of intensive care unit admission and maternal mortality among pregnant women during the second wave of the COVID‐19 pandemic in India 8 .…”
Section: Introductionmentioning
confidence: 51%
“…The most common symptoms reported were fatigue, fever, cough, and anosmia with ageusia (74,77,78). Moreover, living in low-to middle-income countries and having a history of smoking, overweight or obesity, hypertension, diabetes, cardiovascular diseases, or chronic pulmonary diseases were risk factors for developing severe COVID-19 in pregnancy (74,(79)(80)(81). Comorbidities increased the risk of intensive care admission and mortality significantly (80).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
“…Moreover, living in low-to middle-income countries and having a history of smoking, overweight or obesity, hypertension, diabetes, cardiovascular diseases, or chronic pulmonary diseases were risk factors for developing severe COVID-19 in pregnancy (74,(79)(80)(81). Comorbidities increased the risk of intensive care admission and mortality significantly (80). In retrospective studies of pregnant women with confirmed or suspected COVID-19, the risk for pneumonia increased with maternal age above 35 years and lymphopenia, whereas it decreased with gestational age (76,81).…”
Section: Severe Acute Respiratory Syndrome Coronavirus 2 (Sars-cov-2)...mentioning
confidence: 99%
“…Nevertheless, the growing evidence demonstrates an increased risk of severe adverse outcomes from SARS-CoV-2 infection in pregnant compared with non- pregnant women, particularly when infection occurs during late-second and early-third trimesters ( 11 , 12 ). This increased burden of COVID-19 appears to be disproportionately affecting mother-neonate dyads from low- and middle- income countries ( 13 ). An increased risk of severe COVID-19 outcomes in pregnant women is likely attributable to several factors associated with pregnancy including immunological changes leading to dampening of cellular immunity ( 14 ), physiological changes such as reduced lung capacity and increased risk of thromboembolic disease in late pregnancy ( 1 ).…”
Section: Incidence and Burden Of Covid-19 In Pregnant Womenmentioning
confidence: 99%